Distribution of intestinal stem cell markers in colorectal precancerous lesions. Issue 4 (11th September 2015) - Jang, Bo Gun; Kim, Hye Sung; Kim, Kyung Ju; Rhee, Ye‐Young; Kim, Woo Ho; Kang, Gyeong Hoon
Abstract : Aims: Intestinal stem cell (ISC) markers such as LGR5, ASCL2, EPHB2 and OLFM4, and their clinical implications have been studied extensively in colorectal cancers (CRCs). However, little is known about their expression in precancerous lesions of CRCs. Here, we investigated the expression and distribution of ISC markers in serrated polyps and conventional adenomas. Methods and results: Reverse transcription–polymerase chain reaction (RT–PCR) analysis revealed that all ISC markers were up‐regulated significantly in conventional adenomas with low‐grade dysplasia (CALGs) compared with other lesions. RNA in‐situ hybridization confirmed that CALGs exhibited strong and diffuse expression of all ISC markers, which indicate a stem cell‐like phenotype. However, normal colonic mucosa, hyperplastic polyps and sessile serrated adenomas harboured LGR5 + cells that were confined to the crypt base and demonstrated an organized expression of ISC markers. Notably, in traditional serrated adenomas, expression of LGR5 and ASCL2 was localized to the ectopic crypts as in the normal crypts, but expression of EPHB2 and OLFM4 was distributed in a diffuse manner, which is suggestive of a progenitor‐like features. Conclusions: The expression and distribution profile of ISC markers possibly provides insights into the organization of stem and progenitor‐like cells in each type of precancerous lesion of CRC.